Clinical and ultrasound findings of pentalogy of Cantrell in a newborn: A case report - Wang, Dan; Zheng, Bin; Zhai, Bo; Mo, Juan; Yang, Kaihua; Huo, Yaling (Frontiers in Pediatrics, 2022)
Background: Pentalogy of Cantrell is a rare and deadly syndrome, manifesting as intracardiac anomalies and ventricular diverticulum. Echocardiographers have an insufficient understanding of the pentalogy of Cantrell, which may lead to missed diagnosis, especially in cases lacking the most obvious signs. Case summary: One of twin male infants, at a gestational age of 37 weeks, was found with a cardiac murmur and a pulsatile mass in the midline supraumbilical abdomen for 2 days. Admission echocardiography indicated congenital heart disease. A cardiac murmur was detected in the 3-4 intercostal space and extensively spread. The infant was diagnosed with pentalogy of Cantrell by ultrasound and computed tomography angiography (CTA) preoperatively. The patient underwent heart deformity surgery and was followed up for 16 months. The patient’s cardiac structure and function returned to normal. Conclusion: Intracardiac anomaly and ventricular diverticulum are the primary manifestations of pentalogy of Cantrell. Pentalogy of Cantrell may be diagnosed by combining the ultrasound and CTA findings.